Accurate ratios for the calculation of Speech and Language Therapy staffing for health institutions: a systematic review - Rosales Lillo, Felipe; Monichi Valdenegro, Giovanna (Revista de Investigación en Logopedia, 2025)
While the role of Speech and Language Therapy is well-documented, there is no consensus on the optimal method for estimating staffing needs in health institutions. This study aims to determine the accurate ratios for the calculation of Speech and Language Therapy staffing for health institutions. A systematic review with a qualitative approach was performed, including published evidence between 2024 and 2006 in PubMed, Web of Science and SciELO databases. The keywords ‘Speech and Language Therapy’, ‘Speech and Language Therapist’, ‘Staff’ and ‘Staffing’ were included. Of 4,837 reviewed documents, seven were selected for analysis. PRISMA guideline was used for the report. Ratios varied from .025 to 2.000 whole-time equivalent professionals per 10 clinical beds, with higher ratios for stroke, neurological conditions, and critical care patients. Extra staffing may be required for special needs patients or complex cases. Weekend therapy improves health outcomes. Seven-day rehabilitation services are recommended, adjusting staffing ratios accordingly. Stroke patients should receive 45 minutes of rehabilitation daily, while critical care patients require consistent and safe therapy, with service requirements subject to local review. Patient attributable time includes case conferences, ward rounds, report writing, and participation in multidisciplinary team activities. In conclusion, the ratios for Speech and Language Therapy staffing vary between according to pathologies. It is suggested to calculate the staffing according to patients’ pathologies. Also, to develop a unique formula for outpatients, and to update the ratios, as the allied rehabilitation professionals have been increasingly included in multidisciplinary teams.